The Influence of Motivation on the Learning Outcomes of Islamic Religious Education for Students at As-Shofa Islamic High School Pekanbaru - Mahdi, Imam; Risnawati, Risnawati; Fikri Hamdani, M. (Journal of Comprehensive Science, 2025)
Education is a set of strategies used to help people learn knowledge, understanding, and ways of behaving tailored to their specific needs. This study was conducted to determine the influence of learning motivation on student learning outcomes in Islamic Religious Education subjects at As Shofa Islamic High School Pekanbaru. The research methods used are associative quantitative methods with quantitative descriptive data analysis techniques, analysis prerequisite tests using normality tests and linearity tests, hypothesis tests are carried out with simple linear regression analysis and for samples are carried out with purposive sampling techniques. The results of this study show that the learning motivation of students is in the high category, while the learning outcomes of students in the subject of Islamic Religious Education are classified in the medium category. This study provides insight into the importance of learning motivation in improving learning outcomes, especially in Islamic Religious Education subjects. Based on the results of the calculations that have been carried out, a determination coefficient of 0.615 (61.5%) is obtained, meaning that the independent variable (learning motivation) has a strong influence on the dependent variable (learning outcomes), which is 61.5%, while 38.5% is influenced by other factors. This means that there is a significant influence between learning motivation and student learning outcomes. Thus, it is hoped that teachers of Islamic Religious Education in Senior High Schools must always try to increase students' learning motivation, teachers can help students in increasing their motivation to be better so that students have high motivation to learn, and achievement in their learning outcomes is optimal.